THE EFFECT OF COOPERATIVE LEARNING TYPE TGT AND LEARNING MOTIVATION ON READING COMPREHENSION OF PRIVATE VOCATIONAL HIGH SCHOOL STUDENTS (SMK) IN BEKASI - Abdulloh abdulloh (STIBA IEC JAKARTA, 2016)
The purpose of this study are to prove or determine the effect of cooperative learning model type TGT on reading comprehension , to prove or to determine the effect of learning motivation on reading comprehension and to know the interaction effect of cooperative learning and learning motivation together on reading comprehension, especially for Vocational High School (Sekolah Menengah Kejuruan /SMK) students. The study used survey and experiment with analysis model of treatment by level. Anova Two-Way is used to test the hypothesis. Experiment is carried out in two groups or samples, each of them was given different treatment. The first group called Experiment Class, a class that was taught by using cooperative learning type Team Game Tournament (TGT) with combination of reading race, while the second group called a Control class, a class that was taught by using expository method. Each group is then divided into two categories of level of learning motivation. The first group is a group of students with high learning motivation level, the second one with low learning motivation level. The research found that : (1) there is a significant effect of using cooperative learning on students reading comprehension achievement. It shows that sig = 0.000 < 0.05 and Fo=32,846 ; (2) there is a significant effect of the student’s learning motivation on students reading comprehension achievement , with sig = 0.000 < 0.05, and Fo = (52.566); and (3) there is a significant interaction effect together between cooperative learning and student’s learning motivation on students reading comprehension achievement with sig = 0.009 < 0.05 and Fo = 7.252